Intelligence analysis in the knowledge age : an analysis of the challenges facing the practice of intelligence analysis - Duvenage, Magdalena Adriana (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2010.